Evaluation of the bacterial population on the surfaces of stretchers of a University Hospital in Pernambuco (Research, Society and Development, 2021)
Hospital infections (NI) are a major public health problem worldwide and are related to factors such as the inappropriate use of antibiotics, invasive procedures, inadequate hygiene of objects and the hands of health professionals. The present study aimed to isolate, identify and analyze the antimicrobial resistance profile of bacteria present on the surfaces of stretchers of a University Hospital in Pernambuco. This is a descriptive-exploratory study with a quantitative approach carried out in two rooms of a University Hospital. Swab collection was performed on 60 stretchers on the following surfaces: a) Left grid; b) Right grid; c) Upper center and d) Lower center. Surface samples were collected using a filter paper mold with an area of ​​4 cm² and swabs soaked in 0.9% sterile saline solution. After passing the swab on the surfaces, they were stored in a tube containing 5 mL BHI liquid medium (Brain Heart Infusion). Then, the samples were transported to the Clinical Analysis Laboratory/Microbiology Sector, where microbiological and antibiogram analyzes were performed. The overall of bacterial isolates on the litter surfaces was 562, regardless of the sampled location, with 11 species being possible cause of hospital infections, including: Staphylococcus aureus, Acinetobacter baumannii, Klebsiella pneumoniae and Escherichia coli. Regarding the resistance profile, some of these microorganisms showed 100% resistance to the antibiotics tested. These results allow us to conclude that hospital stretchers can reserve resistant bacteria that favor HIs and require hygiene protocols.